Accountability and Transparency of Entrepreneurial Journalism: Unresolved ethical issues in crowdfunded journalism projects. (17th February 2016) - Porlezza, Colin; Splendore, Sergio
Abstract : Crowdfunding is a new business model in which journalists rely—and depend—on (micro-) payments by a large number of supporters to finance their reporting. In this form of entrepreneurial journalism the roles of publisher, fundraiser and journalist often overlap. This raises questions about conflicts of interest, accountability and transparency. The article presents the results of selected case studies in four different European countries—Germany ( Krautreporter ), Italy ( Occhidellaguerra ), the United Kingdom ( Contributoria ) and the Netherlands ( De Correspondent )—as well as one US example (Kickstarter). The study used a two-step methodological approach: first a content analysis of the websites and the Twitter accounts with regard to practices of media accountability, transparency and user participation was undertaken. The aim was to investigate how far ethical challenges in crowdfunded entrepreneurial journalism are accounted for. Second, we present findings from semi-structured interviews with journalists from each crowdfunding. The study provides evidence about the ethical issues in this area, particularly in relation to production transparency and responsiveness. The study also shows that in some cases of crowdfunding (platforms), accountability is outsourced and implemented only through the audience participation.